VISUAL THINKING STRATEGIES BASED PICTURE BOOK MEDIA FOR THEMATIC LEARNING IN ELEMENTARY SCHOOLS - Sutama, Sutama; Wulandari, Nur Asih; Ishartono, Naufal; Narimo, Sabar; Sutopo, Anam (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2020)
The research in this article aims to develop a picture book based on visual thinking strategies for thematic learning in elementary schools. This is specifically intended to test the feasibility of the media developed in aspects of 1) material, 2) media, 3) teacher response, and 4) student response. This research is categorized as research and development. Research subjects for limited trials were teachers and third-grade students of SD Muhammadiyah 16 Karangasem consisting of 2 teachers and 9 students. The type of research is qualitative evaluative. The data were obtained from the validation assessment of material experts, media experts, teachers, and students' responses. The data analysis technique was conducted through flow and constant comparison methods. Based on the results, the assessments of the media developed are 1) material experts earned a score of 62 with suitable category, 2) media experts obtained a score of 45 with suitable category, 3) teacher responses scored 44 with very suitable category, and 4) student responses gained a score of 14.1 with very suitable category. To conclude, the picture book based on visual thinking strategies is suitable for learning media in elementary schools.Penelitian dalam artikel ini bertujuan untuk mengembangkan buku bergambar berbasis strategi berpikir visual untuk pembelajaran tematik di sekolah dasar. Hal ini secara khusus dimaksudkan untuk menguji kelayakan media yang dikembangkan pada aspek 1) materi, 2) media, 3) respon guru, dan 4) respon siswa. Penelitian ini dikategorikan sebagai penelitian dan pengembangan. Subjek penelitian pada penelitian terbatas ini adalah guru-guru dan siswa kelas tiga di SD Muhammadiyah 16 Karangasem yang terdiri dari 2 guru dan 9 siswa. Data diperoleh dari penilaian validasi ahli materi, ahli media, guru, dan tanggapan siswa. Teknik analisis data dilakukan dengan metode perbandingan aliran dan konstan. Berdasarkan hasil penilaian terhadap media yang dikembangkan adalah 1) ahli materi memperoleh skor 62 dengan kategori sesuai, 2) ahli media memperoleh skor 45 dengan kategori sesuai, 3) tanggapan guru memperoleh skor 44 dengan kategori sangat sesuai, dan 4) Respon siswa memperoleh skor 14,1 dengan kategori sangat sesuai. Kesimpulannya, buku bergambar berbasis strategi berpikir visual cocok untuk media pembelajaran di sekolah awal.